KEBERHASILAN PKBI SUMATERA BARAT DALAM MEWUJUDKAN PERILAKU SEHAT KOLEKTIF PADA PROGRAM SANITASI TOTAL BERBASIS MASYARAKAT (STBM) (Suatu Studi Pemberdayaan Komunitas) - Suci Kurnia Sari; Afrizal Afrizal; Indraddin Indraddin (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
The aim of the study was to explain the PKBI West Sumatra strategy to change collective sanitation behavior, community response to the Total Led Community Sanitation (CLTS) program and explain multi-stakeholders who contribute to community empowerment in the CLTS program. Based on the results of the study it was found that PKBI West Sumatra conducted socialization through new empowerment. The community responded to the program very well. Multi stakeholders who contributed during the government, nagari government, community and company. Contributions are financial, energy, and interrelated thinking. Changes that occur in NagariBatangBarus will be seen as a reality that is built and built together towards the direction of external reality and shifts towards the objectification made, accepted into a new reality and obeyed.